Improving Cognitive Abilities in Recognizing Geometric Shapes Material through the Index Card Match Method - Fidiani, Ana; Romlah, Romlah; Primanisa, Reiska (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2023)
This research aims to improve the cognitive ability of group B children at the AL-Ulya Rajabasa Kindergarten in Bandar Lampung to recognize geometric shapes through the index card match method. Due to the lack of learning media, children cannot focus or name geometric shapes. This research uses the classroom action research method with two cycles. The data-collecting techniques employed were observations, interviews, and documentation. The subject of this research was one classroom teacher and twelve AL-Ulya Kindergarten group B students. The analysis shows that the children's cognitive ability to recognize geometric shapes through the index card match method increases. Improvements can be seen after taking action in cycle 1. Two children (16.6%) experienced excellent development. In cycle 2, ten children developed very well (83.3%). This research was stopped in the second cycle because the predetermined standard was exceeded; children who developed very well reached 75%. The results of children's ability to recognize geometric shapes before and after using the index card match method have increased greatly. In the results of observations in research, implementing learning such as using the index card match method can improve cognitive abilities in recognizing geometric shapes.